Zone-specific damage of the olfactory epithelium under protein restriction - Ayinuer Tuerdi (Nature Portfolio, 2020)
Abstract Oxidative stress causes tissue damage, affecting age-related pathologies. Protein restriction (PR) provides a powerful intervention strategy for reducing oxidative stress, which may have a positive effect on individual organs. However, it is unknown whether PR intervention influences the olfactory system. Here, we investigated how 10 months of PR could affect the cell dynamics of the olfactory epithelium (OE) in mice. We found that PR reduced age-related loss of outer hair cells in the cochlea, providing preventive effects against age-related hearing loss. In contrast, PR resulted in reduced mature olfactory sensory neurons (OSNs), increased proliferative basal cells, and increased apoptotic OSNs in zone 1 (the only area containing neurons expressing NQO1 [quinone dehydrogenase 1]) of the OE in comparison with animals given a control diet. Substantial oxidative stress occurred in NQO1-positive cells and induced apoptotic OSNs in zone 1. These results indicate that in contrast to the positive effect on the auditory system, PR induces oxidative stress and structurally and functionally negative effects on OSNs in zone 1, which is probably involved in the bioactivation of NQO1.